DIMENSIONS, MAGNITUDE AND PERSONAL ANTECEDENTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG A SLICE OF HEALTH PROFESSIONALS IN AN EGYPTIAN CONTEXT - Abdel-Aziz, Basem Farouk (International Journal For Research In Business, Management And Accounting, 2021)
Organizational Citizenship Behavior (OCB) is becoming a focus of universal extensive research. Twenty-four itemed Podsakoff et al.'s (1990) OCB questionnaire has been used as an initial item pool to develop an OCB concept measurement model. The study was performed on healthcare professionals conducting their postgraduate studies at High Institute of Public Health, Alexandria University, Egypt. Four successive samples (S1, S2, S3, & S4) were collected one month apart. Preliminary screening procedures revealed that eighteen items were not suitable for factor analysis and were screened out. Six items that survived the screening process were subjected to exploratory factor analysis which disclosed a bifactorial model with three indicators loading on each factor. These initial results were cross-validated through carrying out CFA on a second sample S2 that clarified the factorial validity of the model through adequate global and local fit indices. The model displayed adequate convergent and discriminant validities. The model satisfied the condition of tau-equivalence while parallelism was not fulfilled. Test-retest reliability across consecutive administrations was verified. Multiple-group CFA authenticated model's invariance across S1 & S2. Temporal invariance of the OCB model was established through verifying model's invariance through four sequential samples S1, S2, S3 & S4. Moreover, the model was invariant across various categories of participants' personal attributes including age, gender, marital status, undergraduate merit, tenure, postgraduate program, profession and work sector. All through the study four successive levels of invariance have been ratified. Weighted rather than equal indicator scoring has been used to calculate OCB scale and subscale magnitudes which demonstrated a moderate level of OCB together with its two dimensions, namely, "Civic virtue" and "Conscientiousness". No association has been displayed between OCB and participants' personal characteristics. Based on study findings:- recommendations, managerial implications, future research directions, and limitations have been underscored.